PHYSICAL THERAPY FOR DEFORMITY HAGLUND-SCHINTZ - Nesterchuk, N. Ye.; Udodik, S. R. (Rehabilitation and Recreation, 2023)
Purpose is to describe the features of physical therapy for children and adolescents with Haglund- Schintz deformity. Material. Developmental factors are highlighted, namely, it was found that girls aged 7–8 years, as well as boys aged 9–11 years, are most prone to this ailment. According to the “Regional Public Health Center” (Rivne, Rivne Oblast), every 45th child under the age of 16 has a history of Haglund- Shintz deformity, and therefore the spread of information about physical therapy as the basis of conservative treatment, will prevent the occurrence of complications, and preventive measures will help prevent the development of the disease. The results. Means of physical therapy for patients with Haglund-Shintz deformity are: a complex of therapeutic exercises, therapeutic massage, kinesiotaping and physiotherapy. These tools are used comprehensively and have an individual character. During the study, a program of therapeutic exercises was developed and it was established that the effectiveness of this program is 86.7%. A contraindication to performing this set of exercises is sharp pain while walking. In the stage of full recovery, they begin to perform active movements in the ankle joint, walking on spring devices, classes on exercise bikes are allowed. To prevent Haglund-Schintz deformity in children from progressing, it is recommended to wear heels. Excessive loads on the foot should be avoided. Excessive loads mean, for example, jumping, squatting, running with a special emphasis on the heel. Conclusions. Timely use of physical therapy contributed to the improvement of the patients’ condition, in particular the reduction of pain, swelling and redness in the patients with inflammation of the Achilles tendon, and in the patients with the existing bony growth, the reduction of pain during walking, as well as the improvement of the general condition of the patients.